Ritual Nutuk Beham dalam tradisi lisan Ngassapi Kutai: Kajian etnolinguistik terhadap nilai karakter dan kearifan ekologis - Oktaviani, Suci; Mulawarman, Widyatmike Gede; Hidayanto, Dwi Nugroho; Hudiyono, Yusak; Azainil, Azainil; Suhatmady, Bibit (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to examine the linguistic expressions in the Nutuk Beham ritual speech, which is part of the oral tradition of the Kutai Adat Lawas community. The speech contains folk tales and cultural symbols that have been passed down from generation to generation in the rice harvest ritual. This study uses an ethnolinguistic approach with a descriptive qualitative method. Data was obtained through direct observation, in-depth interviews with traditional leaders and ritual practitioners, and oral documentation collected during the traditional ceremony. The results of the study show that the Nutuk Beham ritual speech contains a distinctive linguistic structure in the form of repetitive and rhythmic oral poetry. It contains symbolic narratives about the origins of rice and stories of sacrifice that form the mythological basis of the community. These linguistic expressions embody values such as respect, responsibility, and religiosity, and reflect ecological wisdom rooted in the harmonious relationship between humans, nature, and food. This study affirms that the Nutuk Beham ritual speech is not merely a cultural heritage but also an educational medium for transmitting noble values within a local context.